IV sodium ferric gluconate complex in patients admitted due to acute decompansated heart failure and iron deficiency. (14th October 2021) - Borreda, I; Zukermann, R; Epstein, D; Marcusohn, E
Abstract: Introduction: Patients suffering from heart failure (HF) and iron deficiency (ID) have worse outcomes. Intra-venous (IV) ferric carboxymaltose has been shown to reduce HF readmissions and improve symptoms in patients with HF with reduced ejection fraction. However, IV ferric carboxymaltose is significantly more expensive than IV Sodium Ferric Gluconate Complex limiting its availability to most HF failure patients around the globe. Methods: This is a retrospective analysis comparing patients admitted due to acute decompensated HF (ADHF) and treated with or without IV sodium ferric gluconate complex on top of standard medical therapy. The study included all patients admitted due to ADHF, with either reduced or preserved EF between January 2013 to December 2018. Results: During the study period, a total of 1856 patients were admitted due to ADHF. Among them 840 patients had an indication for IV iron therapy. Among them 122 (14.5%) patients were treated with IV Sodium Ferric Gluconate during hospitalisation. When comparing the group that was treated with IV iron compared to standard HF treatment no difference was found at one year after the hospitalization regarding reduction in readmissions due to ADHF (27.9% vs 24.8% respectively P=0.54), nor in all-cause mortality (25.4% vs. 25.6% respectively, P=0.99). Conclusion: Treatment with IV Sodium ferric gluconate complex during hospitalization due to ADHF did not show any advantage in reduction of readmission due to heart failure after 1 year follow up. Funding Acknowledgement: Type of funding sources: None.